Reading comprehension in seventh-grade students through Afro-Colombian literature - Cuello Cuello, Lohorquis Esther; Martínez Arredondo, Leonardo Enrique; González Roys, Gustavo Adolfo (Revista UNIMAR, 2023)
Reading comprehension means understanding what is read; involves the ability to extract explicit and implicit information from the text. It is an ability to order ideas and build relationships within what is written. The study was based on this epistemic conception, whose objective was to promote reading comprehension mediated by Mary Grueso’s Afro-Colombian literature, as a didactic strategy with seventh-grade students. Methodologically, the study was framed in the postpositivist paradigm, under the pedagogical action research method. A written test and an observation log were used as instruments. The results indicated that, with the strategy, the students understood the texts read, and made inferences, and arguments on a topic, having consistency in the discourse. In the same way, they managed to increase their communication skills and their reading fluency, in addition to expanding their vocabulary through the use of the dictionary, when finding unknown terms.